Pengaruh Sistem Olah Tanah dan Pemupukan NPK Terhadap Pertumbuhan dan Hasil Tanaman Jagung Manis (Zea mays L.) - Daeli, Ines Junita Putri; Zulfida, Ida; Alfarisi, Salman (UNIVERSITAS LABUHANBATU, 2025)
This study aims to evaluate the effect of soil tillage systems and NPK fertilizer doses on the growth and yield of sweet corn (Zea mays L.). The study was conducted using a two-factor factorial RAK, namely soil tillage (no tillage, minimum, and maximum) and NPK doses (0, 60, 90, and 120 g/plot). The results showed that the maximum soil preparation treatment (O3) and NPK fertilizer rate of 120 g/plot (P3) generally yielded the best results. However, the combination of O1P2 (no soil preparation + 90 g of fertilizer) also showed high yields on certain parameters, indicating the potential for fertilizer efficiency without the need for intensive soil preparation. This study underscores the importance of combining appropriate land management and fertilization practices to sustainably enhance sweet corn productivity. Keywords: sweet corn, soil tillage system, NPK fertilizer, growth, yield